A ideia de representação nas teorias democráticas elitista, republicana e democracia radical, 2010 - Arretche, Zaira Maria da Silva (2011)
This essay examines the concepts of political representation of three contemporary democratic theories. It aims at exploring their theoretical consistency both regarding the democratic process and the electoral representativeness. The elitist theory of democracy, as framed by Joseph Schumpeter, is based upon the assumption that voters lack discernment skills while political elites have leadership capacity. As a result, representation can be grounded on authority formalism, as well as political participation could be restricted to the choice of representatives. Democracy would be ensured by this decision-making method. The republicanist Philip Pettit's theory, by its turn, is based on republican principles. The non-domination ideal requires the active participation of society, not only in the choice of representatives. Instead, the capability to compete in the decision sphere of power would allow voters to recall representatives by means of control mechanisms established by the rule of law. The theory of radical democracy, as framed by Ernesto Laclau and Chantal Mouffe, lacks the prescriptive features of the two previous ones. It is based on a new analytical perspective of society, which breaks with essentialism dichotomy. They propose an agonistic model of democracy, which takes into account the plural nature of manhood, which is antagonistic and affectionate. As a result, this theory frames the role of representatives differently. As theories of representative democracy, these models of representation present themselves as critical operacionalization, with internal contradictions. As a result, they may, on some dimensions, de-constitute themselves either as democratic theories or as theories of representation.